The Effect of Using Plastic Waste as a Media for Making Handicrafts in Grade IV Fine Arts Learning to Increase Student Creativity at Petompon 02 Elementary School - Nahdya Nurul Safitri; A Nurharini; Gunadi; Ianatul Avifah (Indonesia Approach Education, 2024)
The main problem is lack education of students, especially class IV SDN Petompon 02 regarding the proper and correct disposal and use waste, especially plastic waste. Research was carried out by giving pretest questions to control and experimental classes before giving treatment to experimental class, the end of lesson they were given post-test questions after being given treatment the experimental class, data collection was also taken from questionnaires that had been filled by students. Results this research show the increase in student creativity is high category , meaning use plastic waste as a medium for making handicrafts is effectively used in learning to increase student creativity in craft materials from plastic waste. The novelty of this research is fun learning not only increases students' creativity utilizing plastic waste, but also increases the creativity and artistic spirit of class IV students making crafts from plastic waste student creativity. The results of this research, can help readers find out methods and benefits, as well as the importance reprocessing waste into various forms crafts. This research aims to determine student activities and test effectiveness using plastic waste as medium for making handicrafts to increase activity of class IV students SD Negeri Petompon 02.